Evolution of irregular flowering regimes in orchids - Kindlmann, Pavel (Lankesteriana: International Journal on Orchidology, 2016)
Many orchids are characterised by their so-called irregular flowering regime, which is an irregular sequence of flowering, dormant and sterile stages during the life of one individual (Curtis & Green 1953, Tamm 1956, 1972, 1991, Wells 1967, 1981, 1994, Hutchings 1987, Firmage & Cole 1988, Inghe & Tamm 1988, Wells & Cox 1991, Willems & Bik 1991, Whigham & O’Neill 1991, Jones 1998, Hutchings et al. 1998, Willems & Melser 1998, Kindlmann 1999, Kindlmann & Balounová 1999a, 2001, Kindlmann et al. 2002). Here I would like to review alternative hypotheses that aim to explain this phenomenon.